I musei civici umbri, la commissione Guardabassi e il GIS - Latini, Elena (Archeomatica, 2013)
The aim of the project is to investigate the exposure of the murals removed and exhibited in museums and civic propose recovery "virtual" in their historical context and discovers the property of origin. The scope is Umbria, seen as exemplary place for the testing of a model of cultural enjoyment applicable in a general manner for the enhancement appears aware of the history of museums, and archives of their work. The time span is related to the regulations drawn up by the unit when in Umbria Italy was particularly committed the Artistic Committee that has left a ample testimony to the unpublished documents contained in the 14 manuscripts preserved in the Library Augusta. Submitting a proposal dedicated to the Art Gallery of Assisi as an example of experimentation to locate the paintings detached as a result of the Commission's assessments, define the analysis of the places from which they come, the technique of detachment and media.